Alternative of Pothole Area Measurement Based-on Video using Threshold-based Marking and GLCM - Idestio, Barsyah Dwi; Wirayuda, Tjokorda Agung Budi (INKOM Journal, 2013)
One  obstacle  that  causes  the  slow  progress  of  road repairment  is  the  measurement  of  the  pothole  area.  In  this  process, calculation of area in each pothole is done. Measurement process nowadays is manually performed by using a conventional tool (such as roll meter) with the help of human entirely. This research objective is to develop the system for detecting and measuring pothole area, by implementing the threshold-base marking and GLCM method in asphalt surface video. The system consists of two stages starting with candidate pothole detection using threshold-based marking then continued by classification process based on feature vector obtained through the GLCM. The results show that the accuracy rate of 91.67% system with a time of 0.08 seconds to process each frame.keywords: Pothole, Image detection, GLCMSalah satu kendala yang menyebabkan lambatnya perbaikan jalan yaitu pada proses pengukuran kerusakan jalan. Pada proses ini, dilakukan penghitungan luas tiap-tiap kerusakan. Proses pengukuran saat ini dilakukan secara manual menggunakan alat ukur sederhana (roll meter) dengan bantuan tenaga manusia sepenuhnya. Pada penelitian ini dikembangkan suatu sistem deteksi dan pengukuran kerusakan jalan khususnya lubang, berbasis data video, dengan menerapkan threshold-based marking dan GLCM. Sistem terdiri atas 2 tahapan, dimulai dengan mendeteksi kemungkinan area lubang  menggunakan threshold-based marking dilanjutkan dengan klasifikasi berdasarkan vektor ciri yang diperoleh melalui GLCM. Hasil pengujian menunjukkan bahwa tingkat akurasi sistem sebesar 91.67% dengan waktu proses 0,08 detik untuk setiap frame.kata kunci: Lubang jalan, Deteksi citra, GLCM